The Marsh of Gold Pasternak's Writings on Inspiration and Creation - Pasternak, Boris (Studies in Russian and Slavic Literatures, Cultures, and History, 2008)
"Major statements by the celebrated Russian poet Boris Pasternak (1890-1960)about poetry, inspiration, the creative process, and the significance of artistic/literary creativity in his own life as well as in human life altogether are presented here in direct translation of his own words, and are discussed in the extensive commentaries and introduction. The texts range from 1910 to 1946 and are between two and ninety pages long. There are commentaries on all the texts, as well as a final essay on Pasternak's famous novel, Doctor Zhivago, which is looked at here in the light of what it says on art and inspiration. Although universally acknowledged as one of the great writers of the twentieth century, Pasternak is not yet sufficiently ecognized as the highly original and important thinker that he also was. All his life he thought and wrote about the nature and significance of the experience of inspiration, though he avoided the word "inspiration" where possible, as his own views were not